Dissolving Boundaries in the Anthropocene - Tóth, Zsolt (Hungarian Journal of English and American Studies, 2020)
Book review:Kérchy, Anna, ed. Interspecies Dialogues in Postmillenial Filmic Fantasies, special issue of AMERICANA E-Journal of American Studies in Hungary. 13.2 (2017)Kérchy, Anna, ed. Posthumanism in Fantastic Fiction. AMERICANA eBooks, 2018. 237 pages. ISBN 978-615-5423-46-8. EPUB. Open Access.